6.2k views
5 votes
Find the expression for h (x)

Find the expression for h (x)-example-1
User ARich
by
4.9k points

1 Answer

3 votes

Answer:

We have this original function given:


g(x) =-x^2 +5

And we want to transtale vertically downward 4 units this function and we will get the new fnction h(x) and on this case we have to do this transformation:


h(x)= g(x) -4

And replacing we got:


h(x) = -x^2 +5 -4 =-x^2 +1

Explanation:

We have this original function given:


g(x) =-x^2 +5

And we want to transtale vertically downward 4 units this function and we will get the new fnction h(x) and on this case we have to do this transformation:


h(x)= g(x) -4

And replacing we got:


h(x) = -x^2 +5 -4 =-x^2 +1

User Ricardo Costeira
by
5.2k points